Computerized Image Analysis of Mammographic Microcalcifications: Diagnosis and Prognosis - Karahaliou, Anna N.; Arikidis, Nikolaos S.; Skiadopoulos, Spyros G.; Panayiotakis, George S.; Costaridou, Lena I. (IntechOpen, 2012)
None